Covid-19 Pandemic and Pedagogic Learning Innovations in the 'New' Classroom: Views from educators in the Global North and South - Mpofu, Sibongile; Ndlovu, Sipo (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
This study analyzed the educational practices and innovations applied by educators in the Global North and South during the COVID-19 pandemic. The goal was to identify the nuances and factors driving learning innovations in different contexts and the implications for hybridizing higher education. Using case studies of two universities in the USA and Zimbabwe, the objectives were to identify the e-learning platforms employed to meet teaching and learning demands, to unearth other societal factors apart from COVID-19, to shape the utilization of e-learning platforms, and to understand educators' perspectives on their roles in the 'new' classroom. Utilizing e-learning theory, the qualitative research employed in-depth interviews with 19 faculty from both universities. The findings reveal contextual factors such as socio-economic conditions, digital divide, and institutional policies that inform the choice of learning platforms, specifically Zoom in the North and WhatsApp and Google Classroom in the South.